Fasting blood glucose: A mediator of the association between estimated glomerular filtration rate and arterial stiffness in Japanese population with decreased kidney function - Liling Wu; Zhichen Yang; Xiaodan Wu; Xinglin Chen; Wei Cao; Haofei Hu; Qijun Wan (Karger Publishers, 2024)
Introduction: Low estimated glomerular filtration rate (eGFR) is associated with an increased risk of arterial stiffness in participants with kidney damage. It is uncertain whether this association is due to eGFR itself or is mediated by the eGFR-associated increases in fasting blood glucose (FBG). Method: The cross-sectional study included 865 Japanese participants with decreased kidney function, whose eGFR was less than 90mL/min/1.73m², were recruited from individuals who received medical healthcare. The mediating variable was FBG, with eGFR as the independent variable and brachial-ankle pulse wave velocity (baPWV) as the dependent variable. A mediation analysis was used to evaluate the mediating effect of FBG on the association between eGFR and arterial stiffness. Results: The mean age of the participants was 51.69 ± 9.25 years old, with 65.90% individuals being male. The mean values for FBG, eGFR and baPWV were 5.46 ± 0.79 mmol/L, 68.83 ± 10.05 mL/min/1.73m², and 1423.50 ± 247.78 cm/s, respectively. The mediation analysis revealed that eGFR had a significant direct effect on baPWV (β=-25.68 95%CI (-46.42,-7.45), and that FBG played a partial mediating role in the indirect effect of eGFR on baPWV (β=-3.54 95%CI (-11.88,-0.079). Mediation analysis showed that 12.10% of the effect of eGFR on risk of arterial stiffness was mediated through FBG. Conclusion: The study indicated that there is a mediating relationship between eGFR and FBG in people with decreased kidney function, which is associated with the risk of arterial stiffness. Therefore, the importance of FBG as a mediator should be acknowledged and taken into consideration.